THE INTERRELATION OF MUSICAL STYLES IN THE SYMPHONIC CREATION OF COMPOSER TOLKIN KURBONOV - Adurazzokova Mehriban Jalaluddin's Daughter (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the importance of forms, texture, musical means of expression in the symphonic work of the Uzbek composer Tulqin Kurbanov, as well as the issues of interaction of musical styles are highlighted. (in the example of symphony #6)